The Triple Helix Promoting The IFRJ – Campus Engenheiro Paulo de Frontin - Entrepreneurial Ecosystem - Moreira, Juliano dos Santos (2021)
Knowledge-based Society demands new challenges for Educational Institutions whereas they emerge as change agents, making the Academy rise as a leading figure for economic, social and technological development. The present study aimed to analyze aspects regarding the rise of the technological entrepreneurial environment at a rural location and its relationship with academic entrepreneurship fomenting activities promoted by IFRJ - Campus Engenheiro Paulo de Frontin. The research is defined as an exploratory, qualitative case study with multiple data collect methods analyzed through the content analysis method. It was observed in the Campus a strategic move from the traditional academic model towards the entrepreneurial university model, proposed by the Triple Helix Model. Results alowed an academic entrepreneurship fomenting actions categorization, performed by the Campus, capable to promote an entrepreneurial Ethos that led to the creation of developing groups and startups in the studied academic environment. These actors start an external relationship net, that results in an incipient entrepreneurial ecosystem in its location. The study made possible the technological entrepreneurial ecosystem’s description that emerges in contrast to the rural characteristics of the Campus’ location, presenting the ecosystem’s strengths and improvement needs.